Application of mobile client App in standardized training of department of urology resi-dents - Mou PENG; Zhuo YIN; Jin-Rui YANG; Yi-Jian LI; Yu ZHOU; Yin-Huai WANG (Yixue xinzhi zazhi)
To explore the application of mobile client App in standardized training of department of urology residents. We reviewed the problems and difficulties in the process of standardized training of department of urology residents and discussed the application of mobile client App in standardized training of de-partment of urology residents under the information era of big data, as well as its advantages and disadvantages and improvement suggestions.